Development of blood flow velocimeter of vessel position trace type and measurement of its velocity in the elbow flexor and extensor movement - Yuji , HIRAO; Noor Azmi, Azran Azhim; Yohsuke , KINOUCHI (2009)
We have developed a new ultrasound Doppler blood flow velocimeter which had a B-mode image system. A measurement of blood flow velocity was difficult under the movement, because a blood vessel was moved with muscle movement. But, this equipment is able to trace vessel position by using B-mode image. In this paper, attribute and schema of this equipment are explained. As an incidence angle of ultrasound beam changed under the movement, its correction was suggested. The result of application experiment, this equipment was useful for the measurement under the movement.